Real Exchange Rate and External Balance : How Important Are Price Deflators? - Ahn, JaeBin (IMF Working Papers; Working Paper ;, 2017)
This paper contrasts real exchange rate (RER) measures based on different deflators (CPI, GDP deflator, and ULC) and discusses potential implications for the link-or lack thereof-between RER and external balance. We begin by documenting patterns in the evolution of different measures of RERs, and confirm that the choice of deflator plays a significant role in RER movements. A subsequent empirical investigation based on 35 developed and emerging market economies over 1995 to 2014 yields comprehensive and robust evidence that only the RER deflated by ULC exhibits contemporaneous patterns consistent with the expenditure-switching mechanism. We rationalize the empirical findings by introducing a simple model featuring nominal rigidity and trade in intermediate goods as the one in Obstfeld (2001) and Devereux and Engel (2007), which is shown to generate qualitatively identical patterns to empirical findings.